PERSIAN INTERPRETATION OF FINE ART - T. Toshboltaeva (Galaxy International Interdisciplinary Research Journal, 2022)
Alisher Navoi’s work, a classic example of Uzbek classical literature, is a great factor in the rise of the spiritual thinking of mankind. Not only the works of the poet in Turkish, but also his works in Persian, which are an incomparable example of the Zullisonai tradition, are the reason for many studies. In this The article examines the Persian heritage of the poet "Devoni Foni" Alisher Navoi on the example of the analysis of his gazels.